The Legal Research Plan and the Research Log: An Examination of the Role of the Research Plan and Research Log in the Research Process. Issue 3 (2nd July 2016) - Osborne, Caroline L.
ABSTRACT: A new associate exits the office of Senior Partner with a research assignment. She returns to her office, sits down at the keyboard, pulls up her favorite search engine, and begins typing in keywords. This is the usual start to a research project by a novice researcher. This process may result in an answer; however, it is usually little more than an answer. The average attorney jumps into a research question without thinking. 1 This article discusses the basic elements of a legal research plan, recommends designs of research plans, and identifies the role of the research log in the research process.